병원의 홈페이지 관리운영 실태와 병원경영에 미치는 효과 - 황병덕(Byung-Deog Hwang); 임복희(Bock-Hee Im); 이영환(Young-Hwan Lee) (한국콘텐츠학회 논문지, 10(3), 2010)
The purpose of this study is to provide basic information for marketing strategy for hospitals in Busan Metropolitan area by investigating of the web-site management and effect on hospital management about the web-sites managers. Survey of 53 web-site managers was taken between May 1st and May 25th 2008. The survey was carried out to gather information about characteristics of web-site managers and creating, managing and operating process of web-sites and web-sites' effect and information sharing abilities. The results of survey are as follows. First, most of hospitals' web-sites were launched between 2001 to 2005 via outsourcing. Most of hospitals spent about one to three million won for their web-sites and renew web-sites every year. Most of these web-sites have hospital PR, Q&A, and on-line support functions. Second, most of whom participated in survey have agreed that a hospital web-site has influence in hospital management in various categories such as introducing hospital to medical examination, making doctor's appointment, providing patient guidance, providing medical information, and patient counselling. This study shows that effects of web-sites are closely related to web-site satisfaction level. Therefore, to raise the hospital satisfaction level, it is necessary for hospitals to put more efforts in creating web-site that provides more medical information and improved on-line services. 본 연구의 목적은 부산광역시 소재 병원급 이상 의료기관에 근무하는 병원 홈페이지관련 담당 관리자를 대상으로 병원홈페이지 관리 운영 실태와 홈페이지가 병원경영에 미치는 효과를 분석하여 홈페이지를 활용한 마케팅 전략의 기초자료를 제공함에 있다. 이를 위하여 부산광역시 소재 병원급 이상 53개의 병원급 이상의 의료기관 홈페이지 관리자들을 대상으로 2008년 5월 1일부터 5월 25일까지 25일간 연구자가 직접 방문하여 인터뷰와 설문조사를 실시하였다. 병원홈페이지 관리자들의 설문내용은 일반적인 특성, 홈페이지 제작, 관리 운영, 영향, 부가기능, 정보교류 항목으로 구성 하였으며 분석한 결과는 다음과 같다. 첫째, 병원홈페이지 제작관리 및 운영에 있어서는 제작시기는 2001-2005년이며, 외부업체가 주로 관리하고, 제작 목적은 병원소개이며, 1년 기준으로 홈페이지를 개편하고, 100-300만원 미만의 운영예산과 병원소개, 고객만족센터 그리고 온라인 답변 게시가 가장 높은 것으로 나타났다. 둘째, 병원홈페이지 운영에 영향을 미치는 것은 병원소개, 진료예약, 이용안내, 의료정보제공, 고객상담, 진료안내이고 이들은 대부분 병원경영에 영향을 미치고 있다고 인식하고 있었다. 따라서 내부고객만족을 위해 병원홈페이지에 의료정보제공과 메뉴개선은 직원들의 지속적인 관심을 통하여 향상시키도록 노력하여야 할 것이다.